2019
DOI: 10.1002/hbm.24906
|View full text |Cite
|
Sign up to set email alerts
|

A modality‐specific dysfunction of pain processing in schizophrenia

Abstract: Clinical observations showed that schizophrenia (SCZ) patients reported little or no pain under various conditions that are commonly associated with intense painful sensations, leading to a higher risk of morbidity and mortality. However, this phenomenon has received little attention and its underlying neural mechanisms remain unclear. Here, we conducted two experiments combining psychophysics, electroencephalography (EEG), and functional magnetic resonance imaging (fMRI) techniques to investigate neural mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 118 publications
(163 reference statements)
2
10
0
Order By: Relevance
“…Hence, assessing the possible effects of psychological state on pain perception and brain responses and monitoring the baseline brain activity are highly needed when designing experiments for laboratory studies and evaluating pain abnormalities in clinical practice. For instance, the across-session variability should be taken into consideration when (1) examining the test-retest reliability of pain perception from multiple experimental sessions; (2) assessing the habituation effect of pain using repeated painful stimulation over several days; and (3) evaluating the long-term analgesic effect of treatment strategies in clinical practice or basic research. Besides, evidence showed that structural MRI features (e.g., gray matter intensity/volume, cortical thickness, subcortical volume) are highly correlated with pain perception in both healthy subjects 38,39 and chronic pain patients [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, assessing the possible effects of psychological state on pain perception and brain responses and monitoring the baseline brain activity are highly needed when designing experiments for laboratory studies and evaluating pain abnormalities in clinical practice. For instance, the across-session variability should be taken into consideration when (1) examining the test-retest reliability of pain perception from multiple experimental sessions; (2) assessing the habituation effect of pain using repeated painful stimulation over several days; and (3) evaluating the long-term analgesic effect of treatment strategies in clinical practice or basic research. Besides, evidence showed that structural MRI features (e.g., gray matter intensity/volume, cortical thickness, subcortical volume) are highly correlated with pain perception in both healthy subjects 38,39 and chronic pain patients [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon should be considered when designing experiments for laboratory studies and evaluating pain abnormalities in clinical practice.Blood oxygenation level-dependent functional magnetic resonance imaging (BOLD fMRI) can measure human brain activity objectively and enable a deep understanding of neural processing mechanisms. With this technique, the function of pain pathway structures within the central nervous system in states of acute or chronic pain [1][2][3][4][5][6] , during therapeutic and psychological pain interventions 3,7-9 has been extensively investigated. Recently, accumulating studies suggested that fMRI could be used as a technique to elucidate objective biomarkers for the diagnosis of pain 10,11 as the magnitude of neural responses and self-report pain ratings are highly correlated in many situations 12 .However, pain perception is a very subjective experience, and self-report of pain perception reflects a complex mix of physiological and psychological processes, including nociception, emotion, decision making, selfawareness, social cognition, and communicative tendencies 13 .…”
mentioning
confidence: 99%
“…By contrast, some studies have reported hypersensitivity to pain in schizophrenia [13]. This may depend on the character of the pain stimulus [15]. The differentiation of acute from chronic pain is also important.…”
Section: Discussionmentioning
confidence: 96%
“…It seemed more likely that cognitive impairment and the presence of negative symptoms were decreasing the expression of pain. Nevertheless, a recent study investigating neural mechanisms of pain sensitivity in patients with schizophrenia by means of electroencephalography (EEG) and functional magnetic resonance imaging (fMRI) [15] found that schizophrenia patients showed a lower perceived intensity to nociceptive stimuli compared to healthy controls but similar perceived intensity to non-nociceptive somatosensory and auditory stimuli. This suggests that schizophrenia patients respond differently to pain than to other stimuli.…”
Section: Do Location or Severity Of Pain Influence Pain Perception Inmentioning
confidence: 99%
“…The unexpected finding of increased pain perception in patients with SCZ deserves special considerations, since recent studies demonstrated that patients with SCZ ( 31 – 33 ) have a higher pain threshold for pain than the general population and lower measures of pain than do other patients with major psychiatric disorders, particularly bipolar disorder. As expected ( 34 ), patients in early stages of illness had more pain than those with more advanced stages and HC.…”
Section: Discussionmentioning
confidence: 99%